Contribution à l’étude de l’effet anti ulcère du miel et de la propolis - Etude In vivo - BELBACHIR, Imene; BENOUALI, Nour El Houda Yasmine (My University, 2021)
Ulcer is a chronic disease, quite common which is sometimes complicated by causing hemorrhage and / or perforation of the walls of the stomach or duodenum. Traditional medicine offers alternative remedies of which honey and propolis are one most important. The objective of this work is to evaluate, as a preventive measure, the gastro-protective effect of honey and propolis. After seven days of preventive treatment with Sidr's honey (M1 = 1g / kg and M2 = 2g / kg) and propolis (P1 = 0.5g / kg and P2 = 1g / kg) in female rats by the oral route ( gavage), ethanol / HCl in an amount of 0.6 M HCl and 80% ethanol (96 °). The toxicity test at the choised doses showed no effect in experimental rats. The results obtained, pH, acidity, percentage of ulcer, percentage of inhibition, show that honey and propolis give an inhibitory and gastro-protective effect. The histological study shows lesions in the stomach in the ulcerative rats (T +) compared to the control rats (T-), on the other hand the histological appearance of the stomach, in the rats treated with honey and propolis, is similar to that of the control rats (T-). This study shows that honey and propolis exhibit a gastro-protector effect at choised experimental conditions.
Keywords: Honey; Propolis; Gastric ulcer; Stomach; gastro; protector; Rats